Prevalence of Apical Periodontitis in Different Communities: A Meta-Analysis - Miri, Shima Sadat; Khademi, Abbasali; Amirkhani, Zahra; Amiri, Seyed Mojtaba; Goodarzi, Mohammad; Khazaei, Saber (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to perform a meta-analysis on the prevalence of apical periodontitis (AP) in different communities to obtain accurate data on its prevalence. Methods and Materials: The prevalence of AP in different communities based on the number of individuals, teeth and root-filled teeth was searched using electronic databases of ISI Web of Knowledge, PubMed, Scopus and also ProQuest and Springer. The Metaprop meta-analysis was done using the software R version 3.3.0 with Meta package. The Logit transformation method and random-effects model were used to calculate the pooled prevalence. Heterogeneity was tested by the Q-test (P<0.1 represented statistical significance), I2 statistics (25%, 50% and 75% represented low, medium and high heterogeneity, respectively) and 2τ (2τ was calculated by DerSimonian-Laird estimator method). Results: A total of 77 studies were identified to qualify for inclusion into this meta-analysis. The prevalence of AP based on the number of individuals, teeth and root-filled teeth with the pooled prevalence was 0.519, 0.0498 and 0.3828, respectively. Conclusions: The results of the present study can be helpful for policy makers to monitor the dental public health demographically and compare it to other communities; they may be able find the strengths and drawbacks of their oral and dental health program. Keywords: Meta-Analysis; Periapical Periodontitis; Root Canal Therapy